THE INFLUENTS OF ISLAMIC SYMBOLISMS TOWARD THE DECISION OF CONSUMPTION BUYING OF THE FOOD PRODUCTS (A SURVEY CONDUCTED BY A STUDENT OF THE FACULTY OF SYARIAH IAIN MANADO) - Syarifuddin Syarifuddin (IAIN Manado, 2017)
AbstractThis study was conducted to the influents of the Islamic symbolisms toward the decision of consumption buying of the food products. This is a quantitative research. A survey was also involved in this research. Data are also collected through questionnaire to gain an accurate information. Data analysis technique used was a simple regression. The research findings show that Islamic symbolisms have significant influents toward decision to buy food products. That is, t value of p significant is < 0,005 (0,000 < 0, 05) while R square is 0,273 or 27,3 %. In conclusion the influents of Islamic symbols toward the decision on buying have influents as of 27, 3 %. Keywords: Islamic Symbolism, Decision on buying, food products.